THE PRECIPITIN REACTION BETWEEN TYPE III PNEUMOCOCCUS POLYSACCHARIDE AND HOMOLOGOUS ANTIBODY : II. CONDITIONS FOR QUANTITATIVE PRECIPITATION OF ANTIBODY IN HORSE SERA - Heidelberger, Michael (The Rockefeller University Press, 1935)
The experiments recorded above show that in the case of antipneumococcus horse serum or purified antibody the arbitrary immunological procedure (37° for 2 hours, overnight in the ice box) does not permit either the establishment of a true equilibrium or the precipitation of the maximum amount of antibody nitrogen. Analyses of such horse sera for antibody content should therefore be carried out at 0° and the determinations should be allowed to stand in the cold for at least 24 hours in order to insure the completion of the reaction. It is believed that the similarity of the nitrogen: S III ratios in the specific precipitate, whether obtained from whole serum or from purified antibody, and the failure of added serum to influence the amount of nitrogen precipitated show that the absolute chemical method for the estimation of antibody actually measures antibody and not antibody plus a more or less indefinite amount of non-specific protein. An objection to the use of the method is thus shown to be unfounded.